Embodiment in Irish Sign Language Passives - Lorraine Mary Leeson; John Saeed (Teanga: The Journal of the Irish Association for Applied Linguistics, 2020)
Taking a cognitive linguistic approach, this paper explores passive constructions in Irish Sign Language (ISL). Adopting Foley & Van Valin’s (1984) concept of ‘macroroles’, we introduce the prototypical passive construction in ISL, a construction that incorporates several elements including a shift in focus from the Actor to the Undergoer, the recruitment of body partitioning, the use of an empty locus for establishment of an unspecified actor/s, and potentially, a body lean which may be coupled with averted eyegaze. We explore the viewpoint shifts that this construction allows signers, which support the cognitive grammar emphasis on the importance of construal. We also introduce a related category of constructions which recruit the signer’s body as a surrogate for unspecified actors. Unlike the prototypical passive, these constructions are less complex in that they do not recruit body partitioning, body leans or averted eyegaze. However, they are interesting because they seem to demand inferential readings where the surrogate represents external actors or, metonymically, institutions. In particular, we discuss the use of the signer’s body to represent an unspecified Actor and consider the role of embodiment as a lynchpin for understanding how passives operate. We present examples from the Signs of Ireland corpus and from the European Commission funded Medisigns project to illustrate these constructions in ISL.